Analisis Kemampuan Literasi Matematika dan Keterampilan Berpikir Mahasiswa Ditinjau dari Level Kemampuan Matematika dalam Pisa - Putriyani Samsul; Suarti Djafar (Edumaspul: Jurnal Pendidikan, 2018)
This research was a descriptive qualitative research which aims to describe the characteristics of the level of mathematics literacy skills and students' thinking skills in terms of the level of mathematical ability in PISA. Data collection methods used in this study were written tests and interviews. The main instrument of this study was the researcher himself who was assisted with assistive instruments in the form of PISA mathematics questions, and interview guidelines. The results showed that all subjects met the indicators of level 1 PISA math ability and were the highest level for Subject 2. So that the level of mathematical literacy ability in Subject 2 was at level 1 and thinking skills were in Low Order Thinking. Indicator of PISA mathematics ability level 6 was fulfilled by Subject 3 and Subject 4. So that the level of mathematics literacy ability in Subject 3 and Subject 4 was level 6 and thinking skills were at the High Order Thinking level.